THE URGENCY OF CONSUMER PERSONAL DATA PROTECTION IN INDONESIA’S FINTECH ECOSYSTEM IN THE ERA OF DIGITAL BUSINESS TRANSFORMATION - Osner Johnson Sianipar; Agus Satory; Iwan Darmawan (International Journal of Cultural and Social Science, 2026)
The rapid growth of the financial technology (fintech) industry in Indonesia as part of digital business transformation has significantly improved public access to technology-based financial services. However, this development has also increased the risks of data breaches and misuse of consumers’ personal information. This study aims to analyze the urgency of personal data protection within Indonesia’s fintech ecosystem, evaluate the effectiveness of the existing regulatory framework, and identify strategies to strengthen legal protection in the digital era. The research employs a normative juridical method using statutory and conceptual approaches through literature review of relevant regulations and scholarly works. The findings indicate that although the Personal Data Protection Law provides a solid legal foundation, its implementation still faces challenges, including low compliance among fintech providers, limited public digital literacy, and suboptimal regulatory supervision. Strengthening data governance, enhancing platform accountability, and improving consumer awareness are therefore essential to build a secure and sustainable fintech ecosystem.